Vendas e gestão de vendas B2B: em direção a um modelo integrativo - Pessoa, José Maria Vita (2020)
B2B Sales and Sales Management is an integral part of the International Sales and Sales Management domain, or simply ISSM. Complex domain, several disciplines, different levels of analysis, multi countries, with no uniform definition, where scholars go deep to evaluate the extension and the directions the domain is taking. In this way, this study provides a Sales and Sales Management integrative model supported by Resource-based View theory, RBV. It also proposes a definition for ISSM, identifies the main challenges that sales organizations and professionals are facing, the main opportunities shown by the market, and the managers' concerns about the future of the subject. The research is performed with executives and the research field is information technology multinational companies. As a contribution, it provides to the academy some directions for future studies, and for the market a management support tool to be used by sales organizations and professionals, and related, because it can help the managers to overcome the challenges and capture the market opportunities.